MENTAL DISORDERS AMONG THE POPULATION DURING THE COVID-19 PANDEMIC - Rajabov , Muzaffar; Ashurov , Zarifjon; Yadgarova , Nargiza; Userbayeva , Roza (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The new coronavirus SARS-CoV-2 was revealed at December 2019 in Wuhan, China, rapidly spread over the world and caused global pandemic. The main clinical feature of COVID-19 is a severe acute respiratory deficiency. With the accumulation of new studies, it is clear that the coronavirus causes neurological damages ranged from light (headache, anosmia) to severe acute (encephalitis, meningitis, cramps, strokes et set) in 1/3 patients with COVID-19. In this review we describe symptoms and neurological manifestations in patients infected SARS-CoV-2, structure of this virus, mechanisms of its penetration in cells, probable pathways of neuronal cells infection and pathogenetic mechanisms of neurological damages. Also we pay special the attention to the beginning and development of psychological and psychiatric problems originated from the pandemic.